2013
DOI: 10.1111/jgh.12264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical effectiveness of the emergent colonoscopy in patients with hematochezia according to the type of bowel preparation

Abstract: In hematochezia patients, the PEG group showed a higher diagnostic rate and lower rate of repeated CFS. However, emergent CFS after an enema only seems to be useful in patients with severe hematochezia or if the bleeding focus can be presumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The frequencies of unexpected adverse events attributable to oral lavage agents do not differ significantly between acute LGIB and non-GI bleeding [75], and bowel preparation has been shown to facilitate the accurate diagnosis of disease and SRH (see CQ13) and enable endoscopic treatment [62]. On the other hand, the rate of reaching the cecum was not high, in the range of 20-70%, among patients who had colonoscopy in the early phase without bowel preparation with oral lavage solution [76][77][78][79], and 6.4% of the patients (22/345) developed fever after colonoscopy [79]. Two retrospective observational studies have investigated the difference in cecal intubation rates between bowel preparation with oral lavage solutions and other bowel preparation methods (e.g., enema) [76,78] and reported a higher rate with the former [76,78].…”
Section: Cq10: Is It Effective To Perform Colonoscopy For Acute Lgib mentioning
confidence: 99%
See 2 more Smart Citations
“…The frequencies of unexpected adverse events attributable to oral lavage agents do not differ significantly between acute LGIB and non-GI bleeding [75], and bowel preparation has been shown to facilitate the accurate diagnosis of disease and SRH (see CQ13) and enable endoscopic treatment [62]. On the other hand, the rate of reaching the cecum was not high, in the range of 20-70%, among patients who had colonoscopy in the early phase without bowel preparation with oral lavage solution [76][77][78][79], and 6.4% of the patients (22/345) developed fever after colonoscopy [79]. Two retrospective observational studies have investigated the difference in cecal intubation rates between bowel preparation with oral lavage solutions and other bowel preparation methods (e.g., enema) [76,78] and reported a higher rate with the former [76,78].…”
Section: Cq10: Is It Effective To Perform Colonoscopy For Acute Lgib mentioning
confidence: 99%
“…In a study conducted by Niikura et al [22], the identification of SRH was improved by colonoscopy (i) when performed within 24 h, (ii) by expert endoscopists who have performed > 1,000 colonoscopies, and (iii) with the use of disposable distal attachments and water-jet systems. Although the primary treatment outcome was not to improve the identification rate of SRH in the studies, other studies have also reported that bowel preparation with oral lavage solutions and colonoscopy performed within 24 h improve the identification rate of SRH [35,71,74,76,83]. Statement: There are several endoscopic hemostatic methods including epinephrine injection, coagulation, clipping, and ligation (EBL and detachable snare ligation), among which ligation is less frequently associated with transition to arterial embolization and surgery, suggesting that it is more effective than the other methods.…”
Section: Cq13: What Endoscopic Findings Of Colonic Diverticular Bleedmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence comparing bowel preparation regimens. A retrospective review comparing polyethylene glycol solution with glycerine or water enemas in patients undergoing colonoscopy for LGIB found higher diagnostic yields and reduced need for repeat colonoscopy in the polyethylene glycol group 40. A retrospective review of complications in patients receiving bowel preparation in LGIB reported that the most common complications were hypotension and vomiting, although no patient experienced aspiration pneumonia and volume overload 28…”
Section: Diagnosismentioning
confidence: 99%
“…However, blood is a potent laxative and if the bleeding point is known to be in the distal colorectum, for example, post-polypectomy bleed or source identified in CTA, an enema and copious washing may suffice (although the use of an enema alone is described by a small, retrospective, proof of concept study) 40. CO 2 with gas exchange should be used to reduce gas explosion risk in poorly prepared colons, and diathermy or argon plasma coagulation use should be carefully considered.…”
Section: Therapymentioning
confidence: 99%